Green manure (Ophiopogon japonicus) cover promotes tea plant growth by regulating soil carbon cycling - Shao, Shuaibo; Li, Zhongwei; Zhu, Yanqi; Li, Yi; Li, Yuanping; Wu, Linkun; Rensing, Christopher; Cai, Pumo; Wang, Caihao; Zhang, Jianmin; Li, Qisong (Frontiers in Microbiology, 2024)
In mountainous tea plantations, which are the primary mode of tea cultivation in China, issues such as soil erosion and declining soil fertility are particularly severe. Although green manure cover is an effective agricultural measure for restoring soil fertility, its application in mountainous tea plantations has been relatively understudied. This study investigated the effects of continuous green manure cover using the slope-protecting plant Ophiopogon japonicus on tea plant growth and soil microbial community structure. We implemented three treatments: one year of green manure coverage, two years of coverage, and a control, to study their effects on tea plant growth, soil physicochemical properties, and soil bacterial and fungal communities. Results demonstrate that green manure coverage significantly promote the growth of tea plants, enhanced organic matter and pH levels in soil, and various enzyme activities, including peroxidases and cellulases. Further functional prediction results indicate that green manure coverage markedly promoted several carbon cycling functions in soil microbes, including xylanolysis, cellulolysis, degradation of aromatic compounds, and saprotrophic processes. LEfSe analysis indicated that under green manure cover, the soil tends to enrich more beneficial microbial communities with degradation functions, such as Sphingomonas, Sinomonas, and Haliangium (bacteria), and Penicillium, Apiotrichum, and Talaromyce (fungi). In addition. Random forest and structural equation models indicated that carbon cycling, as a significant differentiating factor, has a significant promoting effect on tea plant growth. In conclusion, in the management practices of mountainous tea plantations, further utilizing slope-protecting plants as green manure can significantly influence the soil microbial community structure and function, enriching microbes involved in the degradation of organic matter and aromatic compounds, thereby positively impacting tea tree growth and soil nutrient levels.